The Influence of High-Intensity Interval Training (HIIT) on VO2Max Improvement in Futsal Extracurricular Participants at SMAN 5 Malang for the 2024/2025 Academic Year - Santoso, Khafidz Bayu; Yunus, Mahmud (Indonesian Conditioning Coaches, 2024)
This study aims to identify the effect of High Intensity Interval Training (HIIT) on improving VO2Max among futsal extracurricular participants at SMA Negeri 5 Malang during the 2024/2025 academic year. The research utilized an experimental method with a one- group pre-test and post-test design. The sample consisted of all 20 futsal extracurricular participants. Data were collected by measuring VO2Max performance before and after the intervention, with analysis conducted using a t-test and SPSS software. The results indicated a t-value of (6.588), which is greater than the t-table value of (1.729), with a significance level of (<0.001). This finding demonstrates a significant difference in VO2Max values before and after the HIIT intervention. The conclusion reveals that HIIT significantly impacts VO2Max improvement among futsal extracurricular participants. HIIT has proven effective in enhancing aerobic capacity through a structured, intensive training approach. This study contributes to the development of physical training programs, particularly in futsal, and serves as a valuable reference for coaches in designing effective programs to improve VO2Max